Analysis of cell cycle-related proteins in mediastinal lymph nodes of patients with N2-NSCLC obtained by EBUS-TBNA: relevance to chemotherapy response. Issue 7 (4th April 2008) - Mohamed, S; Yasufuku, K; Nakajima, T; Hiroshima, K; Kubo, R; Iyoda, A; Yoshida, S; Suzuki, M; Sekine, Y; Shibuya, K; Farouk, A; Fujisawa, T
Abstract : Background: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is an accurate tool for lymph node staging of non-small cell lung cancer (NSCLC). Most patients with NSCLC require systemic chemotherapy during their treatment, with relatively poor responses. If the response to chemotherapy could be predicted, ideally at the time of the initial bronchoscopic examination, the therapeutic benefit could be maximised while limiting toxicity. A study was therefore undertaken to investigate the feasibility of EBUS-TBNA for obtaining tissue samples from mediastinal lymph nodes that can be used for immunohistochemical analysis, and to stratify patients with molecular-based pN2-NSCLC into chemo-responsive and chemoresistant subgroups who might benefit from tailoring of chemotherapy. Methods: The expression of six cell cycle-related proteins (pRb, cyclin D1, p16 INK4A, p53, p21 Waf1, Ki-67) in mediastinal lymph node specimens obtained by EBUS-TBNA was investigated by immunohistochemistry in 36 patients with pN2-NSCLC. Their predictive role(s) in the response to platinum-based chemotherapy was examined. Results: Immunostaining was feasible in all studied specimens. Univariate analysis revealed that p53 and p21 Waf1 expressions were significantly related to the response to chemotherapy (p = 0.002 and p = 0.011, respectively). Multivariate logistic regression analysis revealed that only p53 overexpression was associated with a poor response to chemotherapy (p = 0.021). Conclusions: These results suggest that EBUS-TBNA is a feasible tool for obtaining mediastinal nodal tissue samples amenable for immunohistochemical analysis. Immunostaining of p53 in EBUS-TBNA-guided specimens may be useful in predicting the response to chemotherapy in patients with N2-NSCLC and helping in the selection of patients who might benefit from certain chemotherapeutic strategies.